Pelatihan Berbasis Kompetensi Menggunakan Aplikasi Media Sosial dan Aplikasi Daring - Rajib Ghaniy; Irmayansyah; Hudori; Dwi Rahmiyati; Leny Tritanto Ningrum; Abdul Hannan; Muhamad Alifa Sulaeman Alifa Sulaeman (LP3M Universitas Binaniaga Indonesia, 2025)
This socialization and training activity aims to enhance participants' understanding of the importance of the Electronic Information and Transactions Law (ITE Law), maintaining digital privacy, and the effective and safe use of social media. Participants were provided with knowledge about digital ethics and the legal consequences related to the use of information technology, especially on social media. Additionally, participants were trained to utilize Instagram Insights to analyze content performance and optimize social media use for marketing and branding purposes. The training also covered effective social media planning and the creation of an account and use of the LinkTree application to facilitate the management of various links in one platform. The results of this activity showed an increased understanding of the importance of digital security and skills in managing social media accounts wisely. Furthermore, participants are better prepared to face digital challenges professionally. As a follow-up, ongoing training, periodic evaluation, and the formation of a digital community are needed so that participants can continue to develop their skills in the digital world